THE RELATIONSHIP BETWEEN ONLINE GAME ADDICTION AND ACADEMIC ACHIEVEMENT OF E-SPORTS STUDENTS - Kharisma Kharisma; Fadliyana Ekawaty; Riska Amalya Nasution; Luri Mekeama; Febri Tri Andini (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Online games have became a popular from of entertainment among adolescents and may lead to addiction, potentially affecting academic achievement. This study aimed to analyze the relationship between online game addiction and students’ academic achievement at SMA Negeri 4 Tanjung Jabung Timur. A quantitative correlational design with a cross-sectional approach was applied. The study involved 46 students in grades XI and XII who played online games and participated in e-sports activities, selected using total sampling. Data were collected using the Game Addiction Scale (GAS-21) and students’ report cards, then analyzed using SPSS with the Kendall’s Tau test. The results showed that most students had severe addiction levels and good academic achievement Statistical analysis revealed a strong and significant negative correlation between online game addiction and academic achievement indicating that higher addiction levels are associated with lower academic performance.